130 An Innovative Ambulatory Echocardiography Service Provides Rapid Access to Tests, Reduces Length of Hospital Stay and Improves Patient Care. (3rd June 2016) - Nowbar, Alexandra; Birkinshaw, Francesca; Goodman, Ben; Lesko, Mehdi; Balaji, Gothandaraman
Abstract : Introduction: Demand for urgent Echocardiography in NHS Hospitals is increasing. 1 Ambulatory care unit provides rapid access to investigations and improved quality of patient care in an outpatient setting. We recently introduced Echocardiography service in Ambulatory Emergency Care Unit (AECU) at Northwick Park Hospital for low-risk cardiac patients presenting with syncope, heart failure and atrial fibrillation. The purpose of this prospective study is to assess the safety and efficacy of this service in a large district general hospital. Methods: The baseline group (n = 710) were all patients admitted to the Acute Assessment Unit (AAU) in 2013 who had an echo that appeared to be discharge-dependent (defined as an echo performed on the day of discharge). The ambulatory group (n = 230) were consecutive patients referred to the new service for echo in the 6 months following the introduction of the service in 2015. We assessed length of stay in days and time to echo result in days in both groups. 30-day readmission, specialty referrals and estimated cost-savings were also assessed in the ambulatory group only. Results: Length of stay was lower in the ambulatory group compared to the baseline group (mean 0.57 ± SD 2.12 vs 5.12 ± 6.96, p < 0.00001). Similarly, time to echo result was lower in the ambulatory group compared to the baseline group (0.82 ± 2.38 vs 2.02 ± 4.22, p = 0.00002) (Figure 1 ). In the ambulatory group (Table 1 ), 25 patients (11%) were re-admitted at 30 days. 98 patients were referred to a specialty, most commonly cardiology (n = 74), neurology (n = 7) and respiratory (n = 5). Approximately 920 bed days were saved by offering echo in ambulatory care (assuming 4 days saved per patient). This amounts to an estimated £253, 000 saving (assuming a cost of £275 per excess bed day) over 6 months. Conclusion: Echocardiography service in Ambulatory Emergency Care Unit reduces length of stay in hospital, provides rapid access to investigations for cardiac patients, with no significant increase in 30 day re-admission rates. The results show a significant cost savings together with improved quality of patient care. Reference: Macdonald MR, Hawkins NM, Balmain S, Dalzell J, McMurray JJ, Petrie MC. Transthoracic echocardiography: a survey of current practice in the UK. QJM . 2008;101(5):345-9. doi: 10.1093/qjmed/hcm135.